Correlated Sensory and Sympathetic Innervation Between the Acupoint BL23 and Kidney in the Rat - Zhang, Zhiyun; Xu, Dongsheng; Wang, Jia; Cui, Jingjing; Wu, Shuang; Zou, Ling; Shen, Yi; Jing, Xianghong; Bai, Wanzhu (Frontiers in Integrative Neuroscience, 2021)
Objective: To investigate the sensory and sympathetic innervation associated with both acupoint “Shenshu” (BL23) and kidney in the rat for insight into the neuronal correlation between the Back-Shu Point and its corresponding viscera. Methods: The BL23 and kidney were selected as the representative acupoint and visceral organ in the rat, in which their local nerve fibers were examined by using a double fluorescent immunohistochemistry with calcitonin gene-related peptide (CGRP) and tyrosine hydroxylase (TH), and their neuronal correlation in the dorsal root ganglia (DRGs), spinal cord, and sympathetic (paravertebral) chain investigated using a double fluorescent neural tracing technique with Alexa Fluor 488 and 594 conjugates with cholera toxin subunit B (AF488/594-CTB). Results: In the local tissue of acupoint BL23 and the fiberous capsule of kidney, there distributed abundantly with nerve fibers of CGRP- and TH-positive expression, representing the sensory and sympathetic innervation respectively. While the sensory neurons associated with acupoint BL23 and kidney were observed separately from thoracic (T) 11 to lumbar (L) 3 DRGs and from T10 to L2 DRGs, and converge in part in T12-T13 DRGs. In addition, postganglionic neurons associated with both acupoint BL23 and kidney were found in the sympathetic chain at the same spinal segments, separately labeled with AF488-CTB and AF594-CTB. Conclusion: Our study demonstrates the neural characteristics of the acupoint BL23 and kidney in the rat from the perspective of the neurochemistry and neural pathways, and illustrates an example in which the neural correlation between the Back-Shu Points and their corresponding visceral organs via the periphery sensory and sympathetic pathways under the physiological state.